ABOUT THE ICONOSTASIS OF THE ST. NICHOLAS CHURCH IN VELIKA HOČA (Heritage, 2025)
The iconostasis from the Church of Saint Nicholas in Velika Hoča was made in 1825 and 1826, for the icon of Saint Nicholas painted by the monk and painter Longinus in 1576–77 and for the throne icons that were painted either at the time of the iconostasis' creation or were already in the church. The iconostasis was made by Petar from Debar, a Mijak master who left an inscription saying that he made it out of wood and painted it. There was an assumption that it was the famous woodcarver Petar Garka, but this cannot be confirmed based on his existing works in Macedonia, such as the iconostasis in the Lesnovo or Bigorski monasteries, and the Church of the Holy Savior in Skopje. The iconostasis from the Church of Saint George Runović in Prizren, which is also attributed to him, and where he worked as both a carver and a painter, has also not been preserved, making it impossible to compare. Petar probably painted everything on the iconostasis in Velika Hoča except the throne icons, whose author was famous painter Aleksije Lazović from Bijelo Polje. These icons of Christ and the Virgin Mary are among his most successful works and it is not clear when they were created, so the most certain is the broader time frame between 1814 and 1825.The iconostasis consists of high parapet panels without carved decoration, already mentioned throne icons, richly decorated imperial doors, painted northern doors, and a zone with two rows with images of prophets and apostles. A carved cross with a painted Crucifixion of Christ is placed at the top. The entire iconostasis is constructed according to aesthetics of that time, with wood carvings combined with painted accents in gold and red and sporadically green. Four valuable inscriptions have been preserved on the iconostasis, from which it can be seen that its construction was created for the most part in 1825, with the imperial doors from the following year, 1826. The great similarities with the iconostasis in the Church of St. Stephen in Velika Hoča indicate that the same master and his team also constructed this altar partition, but its painting waited until the major renovation of the Church of St. Stephen in 1863.
Keywords: iconographer, woodcarver, Petar Debarlija, Aleksije Lazović, woodcut, throne icons, doors, inscriptions